HOLDING THE EXISTENCE IN FIVE POEMS BY MAHMOUD DARWISH - Reza Desmita Yuspianti; Kurnia Ningsih (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue of holding the existence which iis done by Palestinian and to know the contribution of poetic elements; repetition, imagery, metaphor, and tone in revealing the issue of holding the existence. This analysis is related to the concept of Myth by Carl Gustav Jung. The result of this analysis shows that the Palestinian stick to their culture and keep loyalty for holding the existence.